2018
DOI: 10.1016/j.ijdrr.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to a long-term decrease in national lightning fatality rates: case study of the United Kingdom with wider implications

Abstract: Decadal average lightning fatality rates in the United Kingdom have decreased markedly from 1.09 deaths per million population per year (M-1 yr-1) in the 1850s to 0.02 M-1 yr-1 by the 2010s. Factors contributing to the decrease are explored. They include a large reduction in the national workforce engaged in manually-intensive agriculture. Consequently, agricultural workforce deaths fell from 38% of all lightning deaths around 1850 to 9% by 2000. The percentage of the national population living in urban areas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Additionally, the percentage of women in these totals decreased from approximately 59 % to 35 % between 1930 and 2021. For comparison, in the United Kingdom, deaths in the agricultural workforce due to lightning dropped from 38 % of all lightning fatalities around 1850 to 9 % by 2000 (Elsom, 2018). Other factors contributing to the decreasing trend in lightning-related fatalities include an increase in urban populations with predominantly indoor jobs, wider use of lightning conductors, improved weather forecasting, significant advancements in 460 medical services, greater availability of immediate emergency assistance with rapid hospital transport, and increased public awareness of safety measures during thunderstorms (e.g., Curran et al, 2000;Elsom and Webb, 2014;Elsom, 2018;Brázdil et al, 2019).…”
Section: A Broader Context Of Czech Weather-related Fatalities 380mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the percentage of women in these totals decreased from approximately 59 % to 35 % between 1930 and 2021. For comparison, in the United Kingdom, deaths in the agricultural workforce due to lightning dropped from 38 % of all lightning fatalities around 1850 to 9 % by 2000 (Elsom, 2018). Other factors contributing to the decreasing trend in lightning-related fatalities include an increase in urban populations with predominantly indoor jobs, wider use of lightning conductors, improved weather forecasting, significant advancements in 460 medical services, greater availability of immediate emergency assistance with rapid hospital transport, and increased public awareness of safety measures during thunderstorms (e.g., Curran et al, 2000;Elsom and Webb, 2014;Elsom, 2018;Brázdil et al, 2019).…”
Section: A Broader Context Of Czech Weather-related Fatalities 380mentioning
confidence: 99%
“…For comparison, in the United Kingdom, deaths in the agricultural workforce due to lightning dropped from 38 % of all lightning fatalities around 1850 to 9 % by 2000 (Elsom, 2018). Other factors contributing to the decreasing trend in lightning-related fatalities include an increase in urban populations with predominantly indoor jobs, wider use of lightning conductors, improved weather forecasting, significant advancements in 460 medical services, greater availability of immediate emergency assistance with rapid hospital transport, and increased public awareness of safety measures during thunderstorms (e.g., Curran et al, 2000;Elsom and Webb, 2014;Elsom, 2018;Brázdil et al, 2019). In agreement with our study, Holle (2016) reported a significant reduction in lightning fatality rates for Western European countries and others transitioning from predominantly rural agricultural societies to primarily urban ones.…”
Section: A Broader Context Of Czech Weather-related Fatalities 380mentioning
confidence: 99%
“…Such an evaluation would encompass an assessment of the system's reliability, timeliness, and capacity to reach rural areas effectively. Addressing these discernible gaps would facilitate the development of more robust and accessible lightning detection and alert systems tailored for rural areas, ultimately contributing to mitigating the impact of lightning-related disasters and preserving lives (Elsom, 2018).…”
Section: Future Prospects and Emerging Technologiesmentioning
confidence: 99%
“…The other safe location is inside a fully-enclosed metal-topped vehicle [16]. Two thirds of lightning injuries occur outdoors [17]. People work outside like farming and field labour, construction and building maintenance activities, pipefitting or plumbing, telecommunications field repairing works and power utility field repairing activities are most vulnerable in Bangladesh during the lightning strikes as these people do not have immediate protection in lightning.…”
Section: Lightning Safetymentioning
confidence: 99%